Relationship between Participative Administration of School Administrators and School Effectiveness under the Secondary Educational Service Area Office Bangkok 1 - Saengnok , Siwapong; Sathapornwachana, Sakda (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The objectives of this research were 1) to study the participative administration of school administration under the Secondary Educational Service area Office Bangkok 1. 2) to study the school effectiveness under the Secondary Educational Service area Office Bangkok 1 and 3) the Relationship between the participative administration of school administration and the school effectiveness under the Secondary Educational Service area Office Bangkok 1. The sample group consisted of 357 teachers under the Secondary Educational Service area Office Bangkok 1, by simple random sampling. The research instrument was a 5-rating scale questionnaire with an IOC validity level of 0.67-1.00 and reliability at 0.98 .The data were statistically analyzed by using frequency, percentage, mean, standard deviation and Pearson’s product moment correlation. The results of the research were as follows: 1) the participative administration of school administration under the Secondary Educational Service area Office Bangkok1 was at a high level in overall and particular aspects ranking from highest to the lowest mean: participation in evaluation, participation in responsibility and sharing of benefits, participation in implementation, participation in decision-making, 2) The school effectiveness under the Secondary under the Secondary Educational Service area Office Bangkok 1 was at a high level in overall and particular aspects ranking from highest to the lowest mean: adaptation, latency, goal attainment and integrate, and relationship between participative administration of school administration and the school effectiveness under the Secondary Educational Service area Office Bangkok 1 was positively significantly correlated (r=.873) at a statistic significant level of .01.